2020
DOI: 10.3390/nu12010243
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D in Primary Headache–from Potential Mechanism to Treatment

Abstract: Some studies have suggested a link between vitamin D and headache; however, the underlying physiological mechanisms are unclear. We aimed to summarize the available evidence on the relationship between vitamin D and the various subtypes of primary headaches, including migraines and tension-type headaches. All articles concerning the association between primary headache and vitamin D published up to October 2019 were retrieved by searching clinical databases, including: EMBASE, MEDLINE, PubMed, Google scholar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 71 publications
0
47
0
1
Order By: Relevance
“…In another study, it has been reported that serum levels of both vitamin D and vitamin D receptors were lower in subjects with migraine than that of controls (8) . In addition, some studies reported no correlations between the levels of serum vitamin D and some parameters of headache such as aura, severity, and duration (28) . In a few studies, the authors found an increase in migraine attacks in the autumn and winter months and a decrease in vitamin D levels in the same period.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it has been reported that serum levels of both vitamin D and vitamin D receptors were lower in subjects with migraine than that of controls (8) . In addition, some studies reported no correlations between the levels of serum vitamin D and some parameters of headache such as aura, severity, and duration (28) . In a few studies, the authors found an increase in migraine attacks in the autumn and winter months and a decrease in vitamin D levels in the same period.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have been suggested the possible role of hypercalcemia in migraine headaches and proposed that genetically elevated serum calcium over lifetime appears to increase risk for migraine [36]. Moreover, investigators have had attempted to explain a number of pathophysiologic mechanisms of vitamin D and its deficiency in patients with migraine [8]. Among these mechanisms, anti-inflammatory effects of calcitriol, controlling T helper cells, acting as a neuroactive steroid, inhibiting nitric oxide, and suppressing prostaglandin E2 are the most proposed mechanisms [8].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, investigators have had attempted to explain a number of pathophysiologic mechanisms of vitamin D and its deficiency in patients with migraine [8]. Among these mechanisms, anti-inflammatory effects of calcitriol, controlling T helper cells, acting as a neuroactive steroid, inhibiting nitric oxide, and suppressing prostaglandin E2 are the most proposed mechanisms [8]. In addition, clinical trials of supplemental vitamin D in patients with migraine headaches have shown controversial results, and supplementing with vitamin D is not indicated in all patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations